Comparing discovery and conventional learning for elementary students epistemic curiosity - Luvia Indriani; I Wayan Dasna; Ratna Ekawati (Jurnal Bidang Pendidikan Dasar, 2026)
This study aimed to compare the effectiveness of the Discovery Learning model and conventional learning in enhancing fifth-grade elementary students’ epistemic curiosity in science. A quantitative quasi-experimental design with a nonequivalent control group was employed. The experimental group (n = 9) received Discovery Learning instruction, while the control group (n = 15) received conventional learning on the Water Cycle topic. Data were collected using a validated and reliable pre-test and post-test questionnaire assessing three dimensions of epistemic curiosity: observation, consultation, and directed thinking. Data were analyzed using the N-Gain test and independent samples t-test. Results showed that Discovery Learning produced greater improvement in all epistemic curiosity indicators than conventional learning. Discovery Learning was categorized as fairly effective, whereas conventional learning was ineffective. The findings indicate that Discovery Learning is a more effective approach for fostering epistemic curiosity in elementary science education.